996 Evaluating the Effects of Airway Pressure Release Ventilation, a Novel Mode of Ventilation, in Children with Acute Respiratory Failure. (October 2012) - Kambhampati, S; Kache, S; Williamson, J; Roberts, T; Messing, S; Arimura, J
Abstract : Background: The mortality rate of ARDS in children exceeds 50%. Airway Pressure Release Ventilation (APRV), a lung protective mode of mechanical ventilation, allows renal and hemodynamic stability in adults with acute respiratory distress syndrome (ARDS). This retrospective case review surveys the safety and utility of APRV in children with ARDS between April 2010 and November 2011. Methods: This study was conducted at the Pediatric ICU at Stanford. Children on APRV for less than 24 hours or who were placed on ECMO were excluded. Primary measures, PaO2/FiO2 (P/F) ratio and the Oxygenation Index (OI), were assessed prior to and after APRV initiation. Secondary measures were blood pressure, creatinine, and sedation requirements. A paired t-test was performed comparing parameters over time and a mixed linear model with a random effect was used to test for significant differences over time. Results: P/F ratio and OI significantly improved upon conversion to APRV. All of the secondary measures assessed remained stable (data not shown). Conclusion: The rise in P/F ratio and decrease in OI upon switching to APRV indicate an improvement in oxygenation. Stability of cardiac, renal, and sedation parameters further demonstrate the mode's utility. This retrospective study demonstrates safety and efficacy of APRV in a small population of children with respiratory failure.